MeJA-responsive bHLH transcription factor LjbHLH7 regulates cyanogenic glucoside biosynthesis in Lotus japonicus. (27th January 2022) - Chen, Cheng; Liu, Fu; Zhang, Kaixuan; Niu, Xiaolei; Zhao, Hui; Liu, Qiuxu; Georgiev, Milen I; Xu, Xiaoheng; Zhang, Xinquan; Zhou, Meiliang
Abstract: Cyanogenic glucosides (CNglcs) play an important role in plant defense response; however, the mechanism of regulation of CNglc synthesis by the external environment and endogenous hormones is largely unclear. In this study, we found that jasmonates (JAs) promoted the synthesis of CNglcs by activating the expression of CNglc biosynthesis genes in Lotus japonicus . Several differentially expressed basic helix–loop–helix (bHLH) family genes related to the synthesis of CNglcs were identified by RNA-seq. LjbHLH7 can directly activate the expression of CYP79D3 gene, the first step of CNglc synthesis, by binding to the G-box sequence of its promoter. Transgenic plants overexpressing LjbHLH7 exhibited higher relative CNglc content and enhanced insect resistance compared with the wild type. Furthermore, the transcriptional activity of LjbHLH7 was suppressed by the interaction with the L. japonicus JASMONATE-ZIM DOMAIN protein LjJAZ4. Based on these results, we propose that LjbHLH7 acts as an activator and LjJAZ4 acts as a repressor of JA-induced regulation of CNglc biosynthesis in L. japonicus . Abstract : A newly discovered transcription factor that modulates cyanogenic glucoside biosynthesis in Lotus japonicus is induced by jasmonates, activating the expression of the key synthesizing enzyme CYP79D3.